Designing authentic performance tasks and projects : tools for meaningful learning and assessment - McTighe, Jay.; Carbaugh, Eric M.; Doubet, Kristina, 1969- (Alexandria, Va. USA : ASCD, 2020)
"Comprehensive guide to engaging students in active, relevant, and deeper learning as they transfer knowledge, skills, and understandings to the real world"--Provided by publisher.
Implementing performance tasks and projects: What and why -- Designing authentic performance tasks -- Crafting cohesive project-based learning experiences -- Constructing and using evaluation tools to enhance student performance -- Teaching to support student performance on tasks and projects -- Tailoring tasks and projects for all students -- Collaborating to manage projects and performances: a teacher-student partnership -- Creating a performance-based curriculum.
Includes bibliographical references (p. 239-242) and index.
Professional.
Professional
Keywords: Competency-based education; Educational tests and measurements; Project method in teaching; Competency-based education; Educational tests and measurements; Project method in teaching; Instructional and educational works